Unified Finite Integral Associated with Generalized I-function - Haile Habenom; Hagos Tadesse; G. Venkat Reddy (International Journal of Mathematics And its Applications, 2018)
In this paper, the authors established new results by applying definite integrals on the product of $\bar{I}$-function with the hypergeometric function. Several other new and known results can also be obtained from our main theorems.